Pengaruh Implementasi Model Transformasi Digital dan Smart Governance Terhadap Efisiensi dan Akuntabilitas Keuangan Pemerintah Daerah di Tapanuli Selatan - Marpaung, Indra Syahputra; Patriansyah, Wawan (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of smart governance implementation and digital transformation on financial efficiency and accountability within the Regional Government of South Tapanuli. Using a quantitative approach with a correlational study design, this research examines the causal relationship between these variables through multiple linear regression analysis. The findings show that digital transformation has a positive and significant impact on both regional financial efficiency and accountability. This supports existing theories that the adoption of digital technologies, such as electronic planning and electronic budgeting, contributes to simplifying processes, reducing operational costs, and improving transparency in financial management. However, the study also finds that smart governance, when analyzed partially, does not have a significant effect on financial accountability despite showing a strong correlation. This indicates a gap in the comprehensive implementation of smart governance, particularly in areas such as public participation, data openness, and institutional responsiveness. The lack of significant influence may reflect inconsistencies or limitations in policy execution at the regional level. Overall, this research provides contextual empirical evidence that can be used as a reference in designing more effective digital transformation strategies aimed at enhancing both financial efficiency and accountability, thereby supporting the realization of good governance in local government institutions.